Pengaruh Penambahan Onggok Singkong Terhadap Sifat Fisik, Kimia, Sensori dan Kesukaan Bakso Kacang Merah - Widiyatun, Umi Nur; Ardiyani, Elfitri Sarah; Abduh, Setya Budi Muhammad; Al-Baarri, Ahmad Ni'matullah (Agriculture Faculty, 2024)
The texture of structured protein such as meat analogue is distinct due to non-fibrous protein plant protein. Onggok contains dietary fiber which can improve the fibrous texture of meat analogue. The aim of this study was to determine the effect of onggok on the physical, chemical, sensorial properties and consumer preference of restructured red bean protein. The product was made by mixing red bean flour, tapioca, spices followed by boiling for 8 min. In addition, onggok as much as 0, 2, 4, and 6% (w/w) was used as the treatment. Meatball from beef was used as a control. Subsequently, the yield, cooking loss, WHC, water content, total solids, protein, fat, texture, fiber, sensory and preferences of the product were tested and analyzed using ANOVA and PCA. The results showed that the addition of onggok up to 6% had no effect (p0.05) on the water content, WHC, cooking loss, total solids, protein, adhesiveness, springiness, cohesiveness, and preferences, while increased (p0.05) the yield, fat, fiber, and hardness. The restructured red bean protein is lower in water content, WHC, fat, protein, sensory and preference than meatballs. PCA analysis showed different clusters between both the meatballs, which was in line with the ANOVA results